Implementasi Pendidikan Karakter Dalam Pembentukan Perilaku Mandiri Taman Kanak-Kanak Maitreyawira Ketapang - Susanti Susanti; Hosan Hosan; Sonika Sonika (STAB Maitreyawira, 2023)
This research is motivated by the independent attitude of Maitreyawira Kindergarten School Ketapang children who are influenced by the implementation of character education in schools. Therefore, this study aims to find out the method of implementing character education and how its implementation can shape the independent behavior of children in Maitreyawira Kindergarten School Ketapang. The method used is qualitative research through survey and observation methods. The research subject was the observation of several children, then interviews were conducted with the parents of the children and the teachers who taught the children. Data collection instruments were in the form of interview results, documentation in the form of photographs of children's and teacher's activities, and field notes (anecdotes). From the results of observations, four categories were obtained to assess children's independence, namely Belum Berkembang (BM), Mulai Berkembang (MB), Berkembang Sesuai Harapan (BSH), and Berkembang Sangat Baik (BSB). The results of the research on the implementation of the independent behavior of the Maitreyawira Kindergarten School Ketapang children were assessed from 7 indicators, with the BM and MB categories at 0%, the BSH category at 64%, and the BSB category at 36%. The results of this study are expected to be useful as input in implementing character education in schools. The conclusion of this study shows that the implementation of character education has succeeded in shaping children's independent behavior in their daily lives.